Helicobacterpylori eradication following endoscopic resection might prevent metachronous gastric cancer: a systematic review and meta-analysis of studies from Japan and Korea - Yu, Tian-Hang; Bai, Dan; Liu, Kai; Zhang, Wei-Han; Chen, Xin-Zu; Hu, Jian-Kun (Frontiers in Medicine, 2024)
Objectives A systematic review and meta-analysis was performed to evaluate the preventive effectiveness of Helicobacter pylori eradication against metachronous gastric cancer (MGC) or dysplasia following endoscopic resection (ER) for early gastric cancer (EGC) or dysplasia. Methods PubMed, Cochrane Library, MEDLINE, and EMBASE were searched until 31 October 2023, and randomized controlled trials or cohort studies were peer-reviewed. The incidence of metachronous gastric lesions (MGLs) including MGC or dysplasia was compared between Helicobacter pylori persistent and negative groups, eradicated and negative groups, and eradicated and persistent groups. Results Totally, 21 eligible studies including 82,256 observations were analyzed. Compared to those never infected, Helicobacter pylori persistent group (RR = 1.58, 95% CI = 0.98–2.53) trended to have a higher risk of MGLs and significantly in partial subgroups, while the post-ER eradicated group (RR = 0.79, 95% CI = 0.43–1.45) did not increase the risk of MGLs. Moreover, successful post-ER eradication could significantly decrease the risk of MGLs (RR = 0.54, 95% CI = 0.44–0.65) compared to those persistently infected. Sensitivity analysis obtained generally consistent results, and no significant publication bias was found. Conclusion The persistent Helicobacter pylori infection trends to increase the post-ER incidence of MGC or dysplasia, but post-ER eradication can decrease the risk correspondingly. Post-ER screening and eradication of Helicobacter pylori have preventive effectiveness on MGC, and the protocol should be recommended to all the post-ER patients. Systematic review registration: The PROSPERO registration identification was CRD42024512101.